RESPONS PRODUKSI AGROINDUSTRI SE’I BABI TERHADAP PERMINTAAN KONSUMEN (STUDI KASUS PADA USAHA AGROINDUSTRI SE’I BABI BAUN) - Diana Meliani Sabat; Maria Krova; Solvi M Makandolu (JURNAL NUKLEUS PETERNAKAN, 2018)
A case study focused on the agroindustry of Baun smoked pork in the District of Amarasi Barat Regency of Kupang has been conducted from September to October 2016. The aims of the study were: (1) to assess consumer perceptions about the peculiarities of Baun smoked pork; (2) to identify the efforts made by the producer in maintaining the customers; (3) to analyze factors that influence consumer demand, and (4) to analyze the extent of the production response to the demand of smoked pork. Ninety consumer respondents were included in this study following a simple random sampling procedure during 30 days of interviewed (3 respondents/day). The data obtained were descriptively analyzed for both qualitative and quantitative. Cobb-Douglas function was used to analyse the correlation and regression for quantitative data. The results showed that Baun smoked pork had a distinctive taste, with simple way of serving and on time. It also had available lesehan dining facilities. Factors that have a significant effect on the demand of smoked pork were the income and the number of family member. Furthermore, the production of smoked pork is influenced by consumer’s demand and day of production. The smoked pork production did not corresponding with the consumer demand, where the total demand of 2,624 kg per month. Therefore, producers should have the right strategy to maintain their potential consumers through the efforts of increasing the number of pig slaughtered especially at the week end. ABSTRAK Penelitian bertujuan untuk: (1) mengetahui persepsi konsumen tentang kekhasan produk se’i babi Baun; (2) mengidentifikasi upaya produsen dalam mempertahankan pelanggan; (3) menganalisis faktor yang mempengaruhi permintaan konsumen; (4) menganalisis sejauh mana respons produksi terhadap permintaan se’i babi. Pengambilan contoh konsumen sebanyak 90 orang dilakukan secara acak sederhana dengan teknik pengambilan tiga orang per hari selama 30 hari. Data dianalisis secara deskriptif kualitatif dan kuantitatif. Analisis kuantitatif berupa analisis korelasi dan regresi dengan pendekatan fungsi Cobb-Douglas. Hasil penelitian menunjukkan bahwa se’i babi Baun memiliki rasa yang khas, cara penyajiannya sederhana dan tepat waktu serta tersedia fasilitas makan lesehan. Faktor-faktor yang berpengaruh nyata terhadap jumlah permintaan se’i babi Baun yaitu pendapatan dan jumlah anggota keluarga. Selanjutnya, produksi se’i babi Baun dipengaruhi oleh permintaan konsumen dan hari produksi. Produksi belum merespon permintaan konsumen dimana jumlah permintaan sebanyak 2.624 kg per bulan belum dapat dipenuhi oleh produsen se’i babi. Oleh karena itu, produsen harus memiliki strategi yang tepat untuk mempertahankan konsumen potensialnya melalui upaya meningkatkan jumlah ternak babi yang dipotong khususnya pada akhir minggu.